2016
DOI: 10.1007/s11999-015-4386-7
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Early/Mid-term Survivorship and Functional Outcome After Bernese Periacetabular Osteotomy in a Pediatric Surgeon Practice?

Abstract: Background The Bernese periacetabular osteotomy (PAO) is a recognized joint-preserving procedure. Achieving joint stability without creating impingement is important, but the orientation target that best balances these sometimes competing goals has not yet been clearly defined. Moreover, the learning curve of this challenging procedure has not been described. Questions/purposes The purposes of this study were (1) to determine the 10-year survivorship and functional outcome after Bernese PAO in a single-surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…The increased survivorship could be the result of the decreased age at operation [2,3,12,33,57], typically in hips with Chiari or triple osteotomies [2,12,19]. Other possible reasons include the lack of hips with advanced osteoarthritis [14,44,54], a lower followup rate [7,11,23,25,31,32,35,45,53], and a decreased percentage of hips with previous surgery [28,54]. In addition, the current patient series is consecutive and includes the very first cases from a new surgical technique and therefore represent the beginning of the learning curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased survivorship could be the result of the decreased age at operation [2,3,12,33,57], typically in hips with Chiari or triple osteotomies [2,12,19]. Other possible reasons include the lack of hips with advanced osteoarthritis [14,44,54], a lower followup rate [7,11,23,25,31,32,35,45,53], and a decreased percentage of hips with previous surgery [28,54]. In addition, the current patient series is consecutive and includes the very first cases from a new surgical technique and therefore represent the beginning of the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Next, various factors associated with failure that are subject to surgical accuracy are reported (Table 6). These include a postoperative deficient acetabular coverage [1,7,11,14,23,41] as a result of undercorrection or postoperative joint incongruency [11,14,28,57]. In addition, excessive acetabular coverage [11,14], acetabular retroversion [1], or nonspherical femoral head [1,33,56] were reported, which potentially can result in postoperative femoroacetabular impingement.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that 93% to 95% of young patients undergoing PAO (mean age: 25.4-26 years) did not require a hip replacement at 10 years' follow-up. 55,56 There is a paucity of long-term follow-up of PAO. The only long-term study of >30 years' follow-up revealed that as many as 71% of patients continued to progress to develop pain symptoms, have radiographic evidence of osteoarthritis, or require hip replacement after PAO.…”
Section: Figure 10mentioning
confidence: 99%
“…Their overall survivorship at 12.4 years was 75% (95% CI, 68%-80%) after the exclusion of 50 hips resulting from loss to followup [20]. Other highvolume studies have reported a survivorship range between 75% and 93% over 10 years with varying numbers lost to followup [15,18,20,29,40,44]. Survivorship at 12 years in the current study group was 94% (95% CI, 85%-98%).…”
Section: Discussionmentioning
confidence: 50%